The publications of François Crépin (1830-1903). An annotated chronological list - Hoste, Ivan; Hanquart, Nicole (Studium, 2018)
As the author of a flora that was used by generations of amateur and professional botanists and, later in his career, of numerous studies on the taxonomy of genus Rosa, François Crépin has a place among the leading botanists in Belgium in the nineteenth century. See for more information about his life and career, among others, Errera & Durand (1906), Lebrun (1968), Diagre-Vanderpelen (2011) and Hoste & Diagre-Vanderpelen (2018).